Altered firing pattern of single-unit muscle sympathetic nerve activity during handgrip exercise in chronic heart failure - Murai, Hisayoshi; Takamura, Masayuki; Maruyama, Michirou; Nakano, Manabu; Ikeda, Tatsunori; Kobayashi, Daisuke; Otowa, Kan‐ichi; Ootsuji, Hiroshi; Okajima, Masaki; Furusho, Hiroshi; Takata, Shigeo; Kaneko, Shuichi (The Journal of physiology, 2009)
Sympathetic activation in chronic heart failure (CHF) is greatly augmented at rest but the response to exercise remains controversial. We previously demonstrated that single-unit muscle sympathetic nerve activity (MSNA) provides a more detailed description of the sympathetic response to physiological stress than multi-unit nerve recordings. The purpose of this study was to determine whether the reflex response and discharge properties of single-unit MSNA are altered during handgrip exercise (HG, 30% of maximum voluntary contraction for 3 min) in CHF patients (New York Heart Association functional class II or III, n = 16) compared with age-matched healthy control subjects ( n = 13). At rest, both single-unit and multi-unit indices of sympathetic outflow were augmented in CHF compared with controls ( P < 0.05). However, the percentage of cardiac intervals that contained one, two, three or four single-unit spikes were not different between the groups. Compared to the control group, HG elicited a larger increase in multi-unit total MSNA (Î1002 Â± 50 compared with Î636 Â± 76 units min â1 , P < 0.05) and single-unit MSNA spike incidence (Î27 Â± 5 compared with Î8 Â± 2 spikes (100 heart beats) â1 ), P < 0.01) in the CHF patients. More importantly, the percentage of cardiac intervals that contained two or three single-unit spikes was increased ( P < 0.05) during exercise in the CHF group only (Î8 Â± 2% and Î5 Â± 1% for two and three spikes, respectively). These results suggest that the larger multi-unit total MSNA response observed during HG in CHF is brought about in part by an increase in the probability of multiple firing of single-unit sympathetic neurones.